Soft-bodied biota from the middle Cambrian (Drumian) Rockslide Formation, Mackenzie Mountains, northwestern Canada. (9th March 2015) - Kimmig, Julien; Pratt, Brian R.
Abstract: A new Burgess Shale-type Lagerstätte is described from the middle Cambrian (Series 3, Drumian) Rockslide Formation of the Mackenzie Mountains, Northwest Territories, Canada. The Rockslide Formation is a unit of deeper water ramp to slope, mixed carbonate, and siliciclastic facies deposited on the northwestern margin of Laurentia. At the fossil-bearing locality, the unit onlaps a fault scarp cutting lower Cambrian sandstones. There it consists of a succession of shale and thick-laminated to thin-bedded lime mudstone, calcareous sandstone, and greenish-colored calcareous mudstone, overlain by shallower water dolostones of the Avalanche Formation, which is indicative of an overall progradational sequence. The Rockslide Formation is of similar age to the Wheeler and Marjum formations of Utah, belonging to the Bolaspidella Biozone. Only two 1 m thick units of greenish mudstone exhibit soft-bodied preservation, with most specimens coming from the lower interval. However, the biota is common but not as diverse as that of other Lagerstätten such as the Burgess Shale in its type area. The shelly fauna is dominated by the hyolith Haplophrentis carinatus Matthew, 1899 along with sparse linguliformean brachiopods, agnostoid arthropods, and ptychoparioid trilobites. The nonmineralized biota includes the macrophytic alga Margaretia dorus Walcott, 1911, priapulid worms, and the carapaces of a number of arthropods. The arthropods belong to Isoxys mackenziensis n. sp., Tuzoia cf. T. guntheri Robison and Richards, 1981 ; Branchiocaris ? sp., Perspicaris ? dilatus Robison and Richards, 1981 ; and bradoriids, along with fragments of arthropods of indeterminate affinities. The style of preservation indicates that most soft parts underwent complete biodegradation, leaving just the more resistant materials such as chitinous arthropod cuticles. The range of preservation and similarity to the coeval biotas preserved in Utah suggests that the composition of this Lagerstätte is probably representative of the community living on the relatively deep-water ramp or slope during middle Cambrian time in Laurentia. This would argue that the extraordinary diversity of the Burgess Shale at Mount Field is anomalous.